Fiscal competition and the composition of public spending: theory and evidence - Rainald Borck; Marco Caliendo; Viktor Steiner (Institute for the Study of Labor (IZA), 2006)
In this paper, we consider fiscal competition between jurisdictions. Capital taxes are used to finance a public input and two public goods, one which benefits mobile skilled workers and one which benefits immobile unskilled workers. We derive the jurisdictions' reaction functions for different spending categories. We then estimate these reaction functions using data from German communities. Thereby we explicitly allow for a spatially lagged dependent variable and a possible spatial error dependence by applying a generalized spatial two-stage least squares (GS2SLS) procedure. The results show that there is significant interaction between spending of neighbouring counties in Germany.
urn:nbn:de:101:1-20081202229
Keywords: 330; Steuerwettbewerb; Öffentliche Ausgaben; Kommunale Finanzpolitik; Qualifikation; Arbeitsmobilität; Raumwirtschaftstheorie; Ökonometrisches Modell; Theorie